Measuring Tax Avoidance using Effective Tax Rate: Concepts and Implications: Array - Aronmwan, Edosa Joshua; Okaiwele, Izilin Mavis (The Journal of Accounting and Management, 2020)
Lack of consensus on the multifaceted concept of tax avoidance has caused us to witness a plethora of proxies that have been developed to measure and capture tax avoidance for the purpose of empirical analysis. Therefore, this study contributes to the literature on tax avoidance as it seeks to find out the similarity or differences between tax avoidance measures, with specific emphasis on effective tax rate based measures. Conducting the ANOVA and the Games Howell multiple comparison tests on a sample of 673 unbalanced firm-year observations, the study found that there is a significant difference between the examined measures, while the Games Howell test further showed that the H & S measure differs significantly from the ETR based measures. The implication of the findings for researchers is that they are to consider their research objectives before deciding on the measure of tax avoidance to use in their study, as there are significant differences between these measures.